2009
DOI: 10.2174/1874387000903010059
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Tennis Technical Training on Coordination Characterictics

Abstract: The purpose of this study was to investigate the effect of tennis training on balance and hand-eye coordination. We also tried to determine the speed difference of coordination evolution in people who had not previously played ball sports compared with people who had. There were two groups on our research. The first group consisted of 17 male university students who had already played a ball sport aged 22,11 ± 0,98 year. We chose the subjects by searching for athletes who had trained for a sport branch other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…Moreover, to be able to see the movement of the ball and make a deadly stroke towards the opponent, it is necessary to have good eye-hand coordination. This is in line with Sahan and Erman (2009) that as the way the ball impacts the racket and the ball speed can change, the hand-eye coordination gets more important.…”
Section: Results Of Hypothesis Testing Using T Testsupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, to be able to see the movement of the ball and make a deadly stroke towards the opponent, it is necessary to have good eye-hand coordination. This is in line with Sahan and Erman (2009) that as the way the ball impacts the racket and the ball speed can change, the hand-eye coordination gets more important.…”
Section: Results Of Hypothesis Testing Using T Testsupporting
confidence: 77%
“…The duration and the level of attention and concentration can be observed as being important factors in the game of tennis. In principle, if coordination is carried out more seriously with high concentration, it can be handled well since the eye-hand coordination has key role to success in tennis (Sahan and Erman, 2009). Moreover, to be able to see the movement of the ball and make a deadly stroke towards the opponent, it is necessary to have good eye-hand coordination.…”
Section: Results Of Hypothesis Testing Using T Testmentioning
confidence: 99%
“…The better performance of ball sports athletes compared to non-ball sports athletes in performing asymmetric bimanual coordination skills was another result of this study, which can be related to years of practice and experience working with both hands and balls in the ball sports group. Also, the task arranged in this study required high coordination between hand and eye movements, which in various studies it has been confirmed that ball exercises have a positive effect on the eye and hand coordination [41]; therefore, one of the possible reasons for the superiority of the bimanual coordination skills of the ball group can be attributed to the stronger coordination between eyes and. Finally, due to the high importance of bimanual coordination skills in sports success [43], it is expected that sports coaches, especially in the education of younger ages, pay attention to this critical issue.…”
Section: Discussionsupporting
confidence: 72%
“…To the best of our knowledge, despite a few researches who mentioned eye movements when tossing the ball (Knudson et al, 1994) and the eye hand coordination while hitting the ball (Sahan & Erman, 2009), there are no many studies investigating eye hand dominance in tennis (Ziagkas, Mavvidis, Grouios, Laios, 2017). The aim of this study was to investigate the effect of ipsilateral and contralateral eye hand dominance in ATP qualification and in tennis serve performance.…”
Section: Introductionmentioning
confidence: 99%